Diagnosis exjuvantibus of a persistent pleural effusion - José M. Porcel (Greater Baltimore Medical Center, 2013)
The diagnosis of uremia-associated effusion is one of exclusion. A patient with an unexplained chronic pleural exudate, which cleared with dialysis, is reported. The differential diagnosis of pleural effusions in patients with chronic kidney disease and the management of uremic pleuritis is briefly discussed.